Neuro-imaging evaluation after the first afebrile seizure in children: A retrospective observational study. (December 2016) - Al-shami, Rana; Khair, Abdulhafeez M.; Elseid, Mahmoud; Ibrahim, Khalid; Al-Ahmad, Amna; Elsetouhy, Ahmed; Kamel, Hussein; Al Yafei, Khalid; Mohamed, Khalid
Highlights: Younger children are more likely to have imaging abnormalities than older children. Imaging abnormalities are higher in status epilepticus. Focal seizures have a slightly increased incidence of imaging abnormalities. Abstract: Purpose: To evaluate the role of neuro-imaging in children presenting with the first afebrile seizure and determine factors that influence the outcome of imaging in a large paediatric emergency centre. Method: This is a retrospective review of the medical records of all patients presenting with the first non-febrile seizure to a large paediatric emergency centre in the state of Qatar. Seizure classification followed the current ILAE classification system. Imaging was undertaken in our tertiary hospital and all images were reviewed by experienced neuro-radiologists. Student t test was used for statistical analysis. Results: Ninety-six children underwent neuro-imaging following the first afebrile seizure. Of them, thirty-two patients (33%) were reported to have abnormalities. Children below the age of two demonstrated a significantly higher percentage of abnormal imaging (59%); (p = 0.002). Children presenting with prolonged seizures showed a high percentage of imaging abnormalities (58%); (p = 0.003). Children with focal seizures demonstrated a higher percentage of imaging abnormality compared to those presenting with generalized seizures (35% vs 31%). This difference did not reach statistical significance. Conclusion: Children below the age of two demonstrated significantly higher percentages of abnormal imaging (59%), as did children presenting with status epilepticus (58%). Neuro-imaging should be considered in infants and those with focal or prolonged seizures. Neuro-imaging informed decision making in 6–8% of children.